Implementation Of Direct Cash Transfer In Cilegon City - Yulianti, Rachmi; Hakima, Ima (Indonesian Journal of Social Science Research, 2024)
Direct cash assistance is one of the programmes to ease the burden on the lives of underprivileged people in meeting their basic needs. Social assistance is the provision of direct cash assistance in the form of money / goods from local governments to individuals, families, groups and / or communities that are not continuous and selective in nature which aims to protect against possible social risks. The problems of this research are first, the inaccuracy of the target distribution of the direct cash assistance programme. Second, there is a delay in the disbursement of funds, so that the community has to wait a long time and this creates social jealousy. In this study, researchers used George C, Edward's programme implementation theory in which his theory suggests there are four variables that influence programme implementation, namely: Communication, Resources, Disposition, and Bureaucratic Structure. The method in this research uses descriptive research methods with a qualitative approach. Data collection techniques used interview techniques, observation, and documentation related to the research. The results of this study are overall that the Implementation of the Cilegon City Direct Cash Assistance (BLT) Programme has been running but is still not optimal because there are still obstacles or problems that occur in the tasks and functions of the DTKS system.